Phase transition studies of Na3Bi system under uniaxial strain. (28th February 2018) - Nie, Tiaoping; Meng, Lijun; Li, Yanru; Luan, Yanhua; Yu, Jun
Abstract: We investigated the electronic properties and phase transitions of Na3 Bi in four structural phases (space groups P 63 / mmc, P 3 ̄ c 1, Fm 3 ̄ m and Cmcm ) under constant-volume uniaxial strain using the first-principles method. For P 63 / mmc and P 3 ̄ c 1-Na3 Bi, an important phase transition from a topological Dirac semimetal (TDS) to a topological insulator appears under compression strain around 4.5%. The insulating gap increases with the increasing compressive strain and up to around 0.1 eV at a strain of 10%. However, both P 63 / mmc and P 3 ̄ c 1-Na3 Bi still keep the properties of a TDS within a tensile strain of 0–10%, although the Dirac points move away from the Γ point along Γ– A in reciprocal space as the tensile strain increases. The Na3 Bi with space group Fm 3 ̄ m is identified as a topological semimetal with the inverted bands between Na-3 s and Bi-6 p and a parabolic dispersion in the vicinity of Γ point. Interestingly, for Fm 3 ̄ m -Na3 Bi, both compression and tensile strain lead to a TDS which is identified by calculating surface Fermi arcs and topological invariants at time-reversal planes ( k z   =  0 and k z   =   π / c ) in reciprocal space. Additionally, we confirmed the high pressure phase Cmcm -Na3 Bi is an ordinary insulator with a gap of about 0.62 eV. It is noteworthy that its gap almost keeps constant around 0.60 eV within a compression strain of 0–10%. In contrast, a remarkable phase transition from an insulator to a metal phase appears under tensile strain. Moreover, this phase transition is highly sensitive to tensile strain and takes place only at a strain 1.0%. These strain-induced electronic structures and phase transitions of the Na3 Bi system in various phases are important due to their possible applications under high pressure in future electronic devices.